Individualized medicine using intestinal responses to CFTR potentiators and correctors. (October 2016) - Beekman, Jeffrey M.
Summary: Cystic fibrosis transmembrane conductance regulator (CFTR) modulators that target the mutant CFTR protein are being introduced for treatment of cystic fibrosis. Stratification of subjects based on their CFTR genotype has been proven essential to demonstrate clinical efficacy of these novel treatments. Despite this stratification, considerable heterogeneity between subjects receiving CFTR modulators is still observed which remains largely uncharacterized. The CFTR genotype, and additional genetic and environmental factors that impact either tissue‐specific CFTR protein characteristics or the pharmacokinetic properties of treatments will likely determine the individual response to therapy. The development of intestinal biomarkers for CFTR modulators may help to better quantitate individual responses to treatment, with potential to optimize treatments for subjects with limited responses, and the selection of responsive subjects that currently do not receive treatments. Here, recent advances concerning the use of intestinal biomarkers for CFTR modulator treatments are reviewed, with a focus on biomarkers of CFTR function in ex vivo rectal biopsies and in vitro cultured primary intestinal organoids. Their potential value is considered in the context of the current unmet needs for better treatments for the majority of subjects with CF, and individual biomarkers that enable the prediction of long term therapeutic responses to CFTR modulators.Pediatr Pulmonol. 2016;51:S23–S34. © 2016 Wiley Periodicals, Inc.